"It's the Amazon World": Small‐Scale Farmers on an Entrepreneurial Treadmill. (6th April 2018) - McKee, Emily
Abstract: From the vantage point of northern Illinois, this article considers how the availability of organic, heirloom, and other specialty foods through a wider variety of grocery stores and online venues is affecting local food systems. Farmers concerned about these new forms of competition develop coping strategies to woo customers, but many of these strategies demand new skill sets and drain farmers' time and resources away from the fields. How sustainable are local food systems when small‐scale farmers must be not only skilled producers, but marketing gurus, gregarious spokespeople, and public educators as well? More contextually grounded qualitative and mixed‐methods research is needed to help local food advocates and farmers understand and ease this entrepreneurial treadmill. [local food systems, direct market agriculture, small‐scale farmers, competition, United States]